Effect of Financial Knowledge on Mentorship and Training of Youth by Young Life Rwanda of the Selected Groups of the Selected Districts of Rwanda Provinces - Ndagijimana, Etienne; Njenga, Samson (International Journal of Strategic Management, 2024)
Unique Contribution to Theory, Practice and Policy: In conclusion, this analysis highlights the critical role of financial behavior and attitude in influencing the sustainable development performance of non-governmental organizations (NGOs). While financial knowledge did not emerge as a significant predictor, fostering positive attitudes towards finance and encouraging sound financial behaviors within NGOs can enhance their effectiveness in advancing sustainable development goals. Based on the results, it is recommended that non-governmental organizations (NGOs) prioritize initiatives aimed at improving financial behavior and fostering positive financial attitudes among their staff and leadership to enhance sustainable development performance.